The Usefulness of Grammar for Writing - NEMOUCHI, Abdelhak (Journal of Human Sciences, 2007)
The present study investigates the rates of correlation between grammar and writing as revealed by the students’ grades, in the department of Foreign Languages at the University of Constantine. Our study is based on an analysis of students’ marks of grammar and writing obtained over four semesters in 2005 and 2006, since the LMD system was implemented. The comparative analysis of the two subjects seeks to determine how far the teachings in grammar are reflected in those of writing, and whether a student skilled in grammar is inevitably good at writing. Measuring the   degree of connection between the components of the same Teaching Unit is dictated by the supposedly natural coherence and articulation existing between them.  Before classifying two or more subjects within the same Teaching Unit, one should confirm how deep they are connected. The remote objective of such a study would be the adaptation of the appropriate approach to the contents designed